Desempenho agronômico de cultivares de cenoura em função da época de plantio - Gomes, Victor Emmanuel de Vasconcelos (Universidade Federal Rural do Semi-Árido, 2019)
In regions with high temperatures, carrot cultivation is inexpressive, as high temper-atures tend to reduce the size and pigmentation of the root and, consequently, the productivity and quality of the product. However, with the advent of summer cultivars, the cultivation of carrots in these regions has been viable. Therefore, the aim with this work was to evaluate the performance of ten carrot cultivars in relation to the planting season. The experiments were carried out at the Rafael Fernandes Experimental Farm of the Federal Rural Semiarid Univer-sity (UFERSA), in the municipality of Mossoró, RN. Four experiments were carried out in May (Season 1), June (Season 2), July (Season 3) and August (Season 4) in 2017. The exper-imental design was a randomized block with ten treatments and four repetitions. The treat-ments were constituted by carrot cultivars (Brasília, BRS Planalto, Kuronan, Suprema, Na-tiva, Mariana, Melinda, Amanda, Érica and Francine). The evaluated characteristics were: root classification, commercial, non-commercial and total yield, dry plant mass, macronutri-ent contents (N, P, K, Ca and Mg), soluble solids, total soluble sugars, total acidity and beta carotene content. In planting seasons 1 and 2, the highest average yields were obtained, 43 and 45 t ha-1, respectively. These planting times were also the ones that presented the best quality characteristics, highlights to total soluble sugars content, SS / ATT and beta-carotene content. Hybrid cultivars presented better performance in productivity, quality and lower de-mand for macro-nutrients. Brasília, BRS Planalto and Kuronan varieties had the worst per-formance in, virtually, all the evaluated characteristics
Keywords: Daucus carota L.; Adaptabilidade; Qualidade; Produtividade; Daucus carota L.; Adaptability; Quality; Yield; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA